Open perseverance: the sensemaking narrative of startup entrepreneurs - Morente, Fran (2018)
The irruption of startups and entrepreneurs has transformed the economic landscape. Entrepreneurs propose innovative business models that must progressively respond to the viability triad, the complex and uncertain process by which an idea becomes a product. Based on the theoretical and practical contributions of Dervin's sensemaking methodology, the objective of this study is to understand the narrative of entrepreneurs in their creation of meaning, identify the uncertainties, identify the practices used to address these uncertainties, and thus obtain a deep knowledge of the sensemaking mechanisms. The results of 43 interviews with entrepreneurs are presented in the form of a narrative composed of four stages and three major gaps, illustrating the practical ways in which entrepreneurs overcome uncertainty and create metastable sense.